Formal Carers’ Perspectives on Elder Abuse within a Maltese Care Home - Zarb, Lindsay (Magyar Gerontológia, 2024)
This research explores formal caregivers’ perspectives on elder abuse within a Maltese care home, addressing the challenges posed by an ageing population and the growing reliance on long-term care.